Peran Teman Sebaya dalam Meningkatkan Keterampilan Sosial Mahasiswa Introvert Program Studi Bimbingan Konseling Islam IAIN Parepare - Desi; Muhammad Qadaruddin; Nurhakki (Institut Agama Islam Negeri Parepare, 2022)
This research examines (1) the social skills problems of introverted students in the IAIN Parepare Islamic Counseling Guidance study program, (2) the role of peers in improving the social skills of introverted students in the IAIN Parepare Islamic Counseling Guidance study program. The aim of this research is to find out the problems that occur in the social skills of introverted students and to find out the roles of peers in improving the social skills of introverted students. The qualitative research method is to obtain data using interview, observation and documentation techniques. The results of research on the social skills problems of introverted students consist of difficulties in starting conversations during social interactions, introverted students also do not have the ability to show their talents, introverted students are limited in expressing opinions and are unable to express their desires, when in a social group what can be done is being a good listener, in this condition introverted students are unable to adapt to their environment. The role of peers for introverted students is to provide opportunities to express their own desires and feelings, then provide examples to introverted students on how to maintain good communication and relationships with other people and how to initiate communication so that they appear to adapt easily to the environment.